Cobalt-catalyzed regioselective stereoconvergent Markovnikov 1, 2-hydrosilylation of conjugated dienes. Issue 4 (6th December 2017) - Sang, Hui Leng; Yu, Songjie; Ge, Shaozhong
Abstract : The first transition metal-catalyzed stereoconvergent Markovnikov 1, 2-hydrosilylation of ( E / Z )-dienes was effectively achieved with excellent E -selectivities using a cobalt catalyst. Abstract : We report the first stereoconvergent Markovnikov 1, 2-hydrosilylation of conjugated dienes using catalysts generated from bench-stable Co(acac)2 and phosphine ligands. A wide range of E / Z -dienes underwent this Markovnikov 1, 2-hydrosilylation in a stereoconvergent manner, affording ( E )-allylsilanes in high isolated yields with high stereoselectivities ( E / Z = >99 : 1) and high regioselectivities ( b / l up to > 99 : 1). Mechanistic studies revealed that this stereoconvergence stems from a σ–π–σ isomerization of an allylcobalt species generated by the 1, 4-hydrometalation of Z -dienes. In addition, a cobalt catalyst that can only catalyze the hydrosilylation of the E -isomer of an ( E / Z )-diene was identified, which allows the separation of the ( Z )-isomer from an isomeric mixture of ( E / Z )-dienes. Furthermore, asymmetric hydrosilylation of ( E )-1-aryl-1, 3-dienes was studied with Co(acac)2 /( R )-difluorphos and good enantioselectivities (er up to 90 : 10) were obtained.